2012
DOI: 10.1371/journal.pone.0045796
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Biodiversity of Flower-Visiting Invertebrates

Abstract: Estimates suggest that perhaps 40% of all invertebrate species are found in tropical rainforest canopies. Extrapolations of total diversity and food web analyses have been based almost exclusively on species inhabiting the foliage, under the assumption that foliage samples are representative of the entire canopy. We examined the validity of this assumption by comparing the density of invertebrates and the species richness of beetles across three canopy microhabitats (mature leaves, new leaves and flowers) on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 71 publications
2
40
0
1
Order By: Relevance
“…However, recent work has revealed that flowers in tropical rainforests attract a very high density and diversity of beetles (Kirmse et al 2003;Ødegaard and Frame 2007;Wardhaugh et al 2012Wardhaugh et al , 2013a. Moreover, Wardhaugh et al (2013bWardhaugh et al ( , 2015 showed that the host specificity of flower-visiting beetles could be relatively high, introducing the possibility of high regional and global diversity as well.…”
Section: Coleopteramentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work has revealed that flowers in tropical rainforests attract a very high density and diversity of beetles (Kirmse et al 2003;Ødegaard and Frame 2007;Wardhaugh et al 2012Wardhaugh et al , 2013a. Moreover, Wardhaugh et al (2013bWardhaugh et al ( , 2015 showed that the host specificity of flower-visiting beetles could be relatively high, introducing the possibility of high regional and global diversity as well.…”
Section: Coleopteramentioning
confidence: 99%
“…These rare pollinator-flower interactions may be less likely to be recorded in less intensive pollination studies. In contrast, studies that view the flower-invertebrate interaction from the invertebrate's perspective, where flowers are a resource to be exploited and all visitors are recorded, are rare (but see Gottsberger and Silberbauer-Gottsberger 2006;Wardhaugh et al 2012Wardhaugh et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…As our study 11 is one of the few to examine the fauna attracted to flowers in tropical rainforests, it is impossible to know how they generalize to other locations. It seems, however, that there is prima facie reason to expect high levels of specialization rather than low levels.…”
Section: Future Directionsmentioning
confidence: 99%
“…The primary results of our paper 11 was the demonstration that (i) the invertebrate assemblage inhabiting the leaves is not representative of the wider canopy community, and (ii) each microhabitat supports a unique assemblage in terms of species composition, species richness, relative abundances, and density. In particular, flowers constitute a very important, but until now under-appreciated, microhabitat for species richness and abundance.…”
mentioning
confidence: 95%
“…Despite their generally ephemeral life, flowers are important resources for many phytophagous insects (Held & Potter 2004;Wardhaugh et al 2012;Tsuji & Sota 2013). The feeding damage on any structure of developing floral buds or mature flowers before seed coat formation is known as florivory (McCall & Irwin 2006).…”
mentioning
confidence: 99%